National accounts of the Netherlands 2012 - Netherlands. Centraal Bureau voor de Statistiek (The Hague: Statistics Netherlands, 2013)
The Dutch economy was still in recession in 2012, with economic growth dropping to -1.2 percent. This was mainly caused by a further decline in household consumption and fixed capital formation. Household spending fell for the second year in a row. Although gross capital formation revived in 2011, this ended early in 2012. The fixed capital formation dip was mainly caused by the weak housing market. Export growth formed the only expenditure component cushioning the fall in the economy. However, re-exports had a substantially higher share in export growth than the exports of domestic products.Government consumption fell due to the measures taken to limit the government deficit. The government deficit decreased during 2012 to 4.1 percent of GDP, but still remained above the EMU norm. The continuing recession, which started in 2011, caused a sharp rise in unemployment. The poor labour market situation also affected household income, which has fallen five years in a row, partly causing the decrease in household consumption. The national accounts are the official overview statistics of the Dutch economy. These statistics play a central role in economic and monetary policy-making and policy analysis and are indeed the basis of the economic predictions and analyses of the Netherlands Bureau for Economic Policy Analysis.National income, economic growth (GDP growth) and government deficit are important figures in the national accounts. These accounts also present figures on consumption, fixed capital formation, imports and exports, and employment. The national accounts include historical time series for the main macro-economic indicators, some going back as far as 1900.
1. Macroeconomics -- 2. Supply, use and input-output tables - 3. Final expenditure -- 4. Output, consumption and generation of income - 5. Labour -- 6. Sector accounts -- 7. (Sub)sector typically detail data -- 8. Historical data -- 9. SAM-, Environmental-, TSA- and Regional accounts
Keywords: Netherlands; Finance; National income; National income--Accounting